A compact low profile dual‐polarized filtering antenna with metamaterial for wideband base station applications. Issue 1 (1st December 2017) - Xi, Lei; Zhai, Huiqing; Li, Long
Abstract: A compact low profile dual‐polarized filtering antenna with metamaterial for wideband base station applications is proposed in this paper. The antenna is fed by two inverted L type coupled line, artificial magnetic conductor is utilized as the reflector. Meanwhile, a stepped impedance resonator is introduced into the inverted L type feedline to suppress the radiation of the antenna outside the operating band and achieve compact structure. The mentioned antenna has 11.5 mm (0.0958λ0 ) profile and two frequency doubling suppression characteristics. The return loss of the antenna is <–10 dB from 2.5 to 3.2 GHz. The gain of the proposed antenna is greater than 6.5 dB over the operation band. The filtering antenna is processed and fabricated, and the measured results are consistent with the simulation results.